2020
DOI: 10.1108/tqm-05-2020-0120
|View full text |Cite
|
Sign up to set email alerts
|

Beware of side effects on quality! Investigating the implications of home working on work-life balance in educational services

Abstract: PurposeTelecommuting from home is back up on the agenda as a result of the unforeseen challenges brought by COVID-19. Working from home permits to avoid disruption in the ordinary functioning of educational institutions triggered by social distancing. However, home-based telecommuting may have some side effects on employees, especially in terms of work-life balance. Soft Total Quality Management (TQM) initiatives are needed to address these side effects. The article intends to shed light on these issues, provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 58 publications
2
51
1
1
Order By: Relevance
“…More control and choice in work is expected to improve wellbeing (Joyce et al 2010 ), and working from home has been linked to higher job satisfaction (Troup and Rose 2012 ). Finally, Eurofound concluded that telework has mainly positive effects on individual performance (Eurofound 2017 ), although working from home entails problems too, such as unclear boundaries between work and private life (Palumbo 2020 ; Palumbo et al 2020 ; Vittersø et al 2003 ) and lack of interpersonal relationship of colleagues (Webster and Wong 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…More control and choice in work is expected to improve wellbeing (Joyce et al 2010 ), and working from home has been linked to higher job satisfaction (Troup and Rose 2012 ). Finally, Eurofound concluded that telework has mainly positive effects on individual performance (Eurofound 2017 ), although working from home entails problems too, such as unclear boundaries between work and private life (Palumbo 2020 ; Palumbo et al 2020 ; Vittersø et al 2003 ) and lack of interpersonal relationship of colleagues (Webster and Wong 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these considerations, as forecasted by hypothesis 2, teleworking from home had positive implications in terms of remote workers' work engagement. People who worked at home showed greater levels of work-related absorption, dedication and vigor (Palumbo et al , 2020). The increased work engagement of teleworkers is boosted by the perception of organizational support that is generally associated with the flexibilization of working arrangements (Jin and McDonald, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the digital transformation of educational institutions may pave the way for new learning models which are more consistent with the evolving expectations of students and institutional stakeholders (Liu et al, 2020), its repercussions on the quality and safety of the working environment should be carefully assessed and addressed (Palumbo et al, 2020). Because occupational health and healthy workplace initiatives may be not sufficient in counteracting the increased psycho-social risks generated by digitization, some organizational interventions are required to avoid the drawbacks of the educational institutions' digital transformation (Dobrovsk a and Andres, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Literature has reviewed both the advantages and the challenges which are triggered by the digital transition of educational institutions, envisioning digitization as a way to achieve people-centeredness in the provision of learning experiences (Gonzales, 2019). Among the challenges which are heralded by digitization, particular relevance is attached to its implications on the workplace climate (Palumbo et al, 2020). The increased pervasiveness of ICTs and digital tools may exacerbate time pressures perceived by educators in accomplishing their organizational tasks, leading to a greater work-related stress (Pareto and Willermark, 2014).…”
Section: Conceptual Backgroundmentioning
confidence: 99%